An XR Framework Proposal to Assist Designers in Minimizing Cybersickness - Santiago, Leonardo Giuri; Kronemberger, Victhor Alves; Porcino, Thiago; Cherullo, Renato; Raposo, Alberto (Anais Estendidos do Simpósio de Realidade Virtual e Aumentada (SVR), 2024)
Extended Reality (XR), as a form of human-computer interaction, continues to encounter significant challenges related to user well-being. The frequent discomfort experienced during the use of head-mounted displays (HMDs), commonly referred to as cybersickness, has been the focus of extensive research. This research has led to the development of various techniques aimed at mitigating these adverse effects. However, there remains an absence of a streamlined, automated method to implement these measures effectively. This project seeks to address this gap by providing developers with a tool that facilitates the easy and modular implementation of cybersickness mitigation techniques. Utilizing game engine events as triggers, this prototype allows for the activation and deactivation of these techniques in a seamless manner. We believe this approach will not only simplify the application process for developers but also promote the broader adoption of VR by enhancing user comfort and overall experience.